Edukasi Pencegahan HIV/AIDS Pada Remaja - Evi Ni’matuzzakiyah (STIKes Ibnu Sina Ajibarang, 2024)
The incidence of HIV transmission and AIDS infection in adolescents is increasing and is still one of the world's centers of attention in terms of health issues. Education is a process of providing health education about HIV-AIDS prevention in order to increase the knowledge and attitudes of adolescents. The aim of this educational program is to increase knowledge and attitudes towards HIV/AIDS prevention. Education is carried out at Madrasah Aliyah Negeri 4 Bantul Yogyakarta. The target of this education is teenagers, who in fact are class XI students at MAN 4 Bantul, totaling 73 people. The design of this activity is to carry out one measurement up front (pre test) before the treatment and after that another measurement is carried out (post test). In this activity, the non-parametric Wilcoxon test is used because the results of the data are not normally distributed. The results show that there is a significant increase in knowledge regarding HIV/AIDS prevention where the p value is 0.004 < 0.05, and there is no significant increase in attitudes towards HIV/AIDS prevention where the p value is 0.138 > 0.05.